If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 3 + -7x = 11 Reorder the terms: 3 + 8x + -7x = 11 Combine like terms: 8x + -7x = 1x 3 + 1x = 11 Solving 3 + 1x = 11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 1x = 11 + -3 Combine like terms: 3 + -3 = 0 0 + 1x = 11 + -3 1x = 11 + -3 Combine like terms: 11 + -3 = 8 1x = 8 Divide each side by '1'. x = 8 Simplifying x = 8
| 16w^2+27=0 | | 36x^2+12x+64=0 | | 12=8n-1 | | 3w-11w=48 | | 6=4x-9y | | 5(1.2k+6)=7.1+34.4 | | -7(6x+1)=-133 | | (9x^2)-252x+330=0 | | x-4x+3=-30 | | -3(3n-8)=30 | | p=-3*4+1 | | 3.2/16= | | (3x-4w)(5x-8w)= | | 8-4x=9-5x | | p=-3q+1 | | -3(4-3y)=3y+6 | | 2(6x+8)-5=12x+11 | | (2+3)x(3+3)=x | | 0.51m+0.03=0.4m-0.74 | | -7(k-1)-5=-2(k-6) | | 26=6(5+-1a) | | 7x+15=3(2-y) | | 5z+15=4z+5 | | y^2+4=400 | | [x/3-6]=(2x+4)(-1/2) | | 8y-3=-3 | | 20=3-(z+10) | | 3x+30=x | | -3(t-2)+9t=8t-6 | | -31-a=-(1-4a) | | 3x+30= | | -3(5y-9)-y=-3(y-3) |